ISLAM, ISLAMISM, THE NATION, AND THE EARLY INDONESIAN NATIONALIST MOVEMENT (State Islamic University (UIN) of Sunan Ampel Surabaya, 2007)
In an attempt to understand better the failure of Islamism to exercise any significant impact on the trajectory of Indonesian politics through the twentieth century, this article examines the development of Indonesian Islamist thought in the early twentieth century and compares it to the growth of secularist nationalist thinking. Islamist thinking was slow to arrive at a consciousness of Indonesia as specific national place and homeland. By the time Islamist thinkers had begun to develop a clearer sense of their own political project, secular nationalist thinkers (often indifferent to and sometimes fiercely opposed to Islamic and Islamist ideas about the relationship of state to religion) had already established the unassailable primacy of the idea of Indonesia as an independent sovereign state-in-the-making and as the vehicle for Indonesians to become both modern and prosperous. Islamists thereafter had no option but to seek to accommodate their thinking to the dominant paradigm of the idea of Indonesia.